The role of the workshop profesional praktice in the educational process in mechanical engineering studies in Novi Sad - Novaković, Dragoljub; Gatalo, Ratko; Hodolič, Janko (Journal of Production Engineering, 1992)
Acceptance of practical knowledge by students participating in the production process is a form of education that facilitates the application and integration of knowledge from various scientific disciplines. This practical knowledge plays a crucial role in technical education as it enhances students' understanding of theoretical concepts and equips them with the skills needed to perform practical tasks, thus molding engineers with a more comprehensive skill set. With a primary aim to enhance the educational process, this paper conducts a detailed analysis of the outcomes achieved during a practical course at the Institute. Building on previous assumptions, it briefly presents the investigation's results, emphasizing the importance of these subjects in the education of graduating mechanical engineers. It further delves into the allocation of time for teaching practical knowledge subjects, analyzing relevant changes and reviewing the evolution of subject programs. Additionally, the paper examines the material, personnel, and program content of these subjects to provide a comprehensive view of their significance in technical education.